Acoustical Comfort Amphiteater Classroom Building B Faculty of Law Universitas Brawijaya - Lita Hilviana Kusnadi (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
The magnificent aspect of form is one of the goals of a design. The shape of a design affects other elements. One of them is the element of comfort. In the classroom design the amphitheater has problems on the acoustic comfort aspect. This makes the lecturer's voice  clearless. Acoustic problems in the classroom can disrupt the activity inside. So the need for the evaluation of acoustic comfort in the classroom of this amphitheater and design recommendations for acoustic conditions in the classroom to support the activities in it. Data collection is done by using kesioner distribution and measurement directly, then the data is calculated using the sabine formula that serves as an indicator of time changes buzzing inside the class, sound absorbing material as an independent variable in modification. Classroom conditions that have many flat planes facing each other cause original sound to be reflected in many reverberant fields and result in reflection sound to reduce clarity to the original sound desired. The use of sound absorbing material can reduce the humming time in the classroom. So the condition of acoustic comfort in this classroom becomes better. Keywords: Aesthetics, Comfort Acoustics, Amphitheater Room, Flutter eco